Resiliensi Sistem Pangan Pertanian sebagai Solusi Disparitas Ketahanan Pangan untuk Mendorong Kesejahteraan Petani di Jawa Tengah - Lestari, Retna Dewi; Suhatmi, Erna Chotidjah; Purnomo, Singgih (Universitas Galuh, 2026)
Food security disparities in Central Java result in inequality in production, market access, and farmers' welfare. The threat of climate change and limited access for farmers to capital and technology further exacerbate this condition. The low selling price of crops compared to production costs is also a major challenge. Therefore, building the resilience of agricultural food systems is a crucial solution to improve adaptation to change and create more inclusive and sustainable agriculture. This study aims to analyze the resilience of the agricultural food system in overcoming food security disparities and improving the welfare of the community in Central Java Province. The data analysis method used includes a quantitative approach using simple linear regression linear analysis and descriptive analysis. In the results of the multiple linear regression test analysis, F test of 29.781 was produced with a very significant p value of 0.0. The results of the t-test showed that food resilience had a significant positive effect (t=5.5659; p=0.0), while food security disparity had a significant negative effect (t=3.3169; p=0.0013). The results of the study showed that 16 districts/cities were in the medium, 10 low, and 9 high categories in their food security levels, spatial analysis showed inequality between regions. Low regions are vulnerable to supply chain shocks and disasters, while high-resilience regions typically have biophysical, infrastructural and commodity diversification advantages. Strengthening resilience through irrigation rehabilitation, salinity-tolerant varieties, weather-based insurance, and equitable access to technology and resources are some of the policy impacts. The findings show that improving food security and reducing disparities can improve farmers' well-being in a sustainable manner.